Sequestration of Atmospheric Carbon through Ocean Calcifiers: An Approach towards Climate Change - David Moore; Matthias Heilweck; William Burton Fears; Peter Petros; Samuel J Squires; Elena Tamburini; Robert Paul Waldron (Innovations in Biological Science Vol. 6, 2024)
This study highlights the potential of ocean calcifiers to sequester atmospheric carbon in quantity and even reverse climate change. The study, which we hope will show why cultivating calcifiers in the short term would be advantageous, attempts to provide a different, biological, viewpoint of the published data bearing on two specific issues, namely ocean acidification and return of CO2 to the atmosphere by the calcification reaction itself. We find reasons to doubt the validity of both issues. Experiments showing ocean acidification is damaging to calcifiers have all used experimental pH levels that are not projected to be reached in the oceans until the next century or later; today’s oceans are alkaline. In open water habitats in equilibrium with the atmosphere, it may be true to claim precipitation of CaCO3 by calcification as a net source of atmospheric CO2, but only if the solidified limestone is ignored as sequestered CO2. In these kinds of conditions, the calcification response is not carried out by living calcifiers. The chemistry of life is distinguished from that of open water by occurring on enzyme polypeptide surfaces, inside organelles with phospholipid membranes that selectively absorb certain ions, and inside cells encased in phospholipid bilayer membranes. Nowadays, marine calcifiers (coccolithophore algae, Foraminifera [protists], Mollusca, Crustacea, Anthozoa [corals], Echinodermata and some annelids) convert atmospheric carbon dioxide (CO2) into solid calcium carbonate (CaCO3) protective shells which are left when they die. These organisms could be the biotechnological carbon capture and storage mechanism to control climate change. Ignoring what is known about the biology, physiology, and molecular biology of living calcifiers leads to erroneous conclusions and deficient advice about the potential for calcifier biotechnology to contribute to atmosphere remediation. We conclude that the world’s aquaculture industries already operate biotechnology that, with massive and immediate global expansion, can sustainably control atmospheric CO2 levels at a reasonable cost. We hope that this view of marine calcifiers will show the value and promise of the contribution that aquaculture could make to bringing equilibrium to the atmosphere.